High-Intensity Intermittent Exercise and Fat Loss - Stephen H. Boutcher (Journal of Obesity)
The effect of regular aerobic exercise on body fat is negligible; however, other forms of exercise may have a greater impact on body composition. For example, emerging research examining high-intensity intermittent exercise (HIIE) indicates that it may be more effective at reducing subcutaneous and abdominal body fat than other types of exercise. The mechanisms underlying the fat reduction induced by HIIE, however, are undetermined. Regular HIIE has been shown to significantly increase both aerobic and anaerobic fitness. HIIE also significantly lowers insulin resistance and results in a number of skeletal muscle adaptations that result in enhanced skeletal muscle fat oxidation and improved glucose tolerance. This review summarizes the results of HIIE studies on fat loss, fitness, insulin resistance, and skeletal muscle. Possible mechanisms underlying HIIE-induced fat loss and implications for the use of HIIE in the treatment and prevention of obesity are also discussed.